THE EFFECT OF EMOTIONAL INTELLIGENCE, WORK STRESS, AND JOB SATISFACTION ON EMPLOYEE PERFORMANCE AT KPKNL DENPASAR - Dinan Silmi Iskandar; Ni Made Ary Widiastini; I Nengah Suarmanayasa (Universitas KH. Abdul Chalim Mojokerto, 2026)
Employee performance is a key factor in improving the quality of public services, particularly in government institutions that face high workloads and performance targets. KPKNL Denpasar has shown an upward trend in its Organizational Performance Score over the past five years. However, it still ranks lowest compared to similar work units within the DJKN Regional Office of Bali and Nusa Tenggara environment. This condition indicates the presence of internal factors affecting employee performance. This study aims to analyze the influence of emotional intelligence, work stress, and job satisfaction on employee performance at KPKNL Denpasar. The research employs a quantitative approach using a survey method administered to all employees of KPKNL Denpasar. Data were collected through questionnaires and analyzed using multiple linear regression analysis. The results indicate that emotional intelligence and job satisfaction have a positive and significant effect on employee performance, while work stress has a negative and significant effect on employee performance. Simultaneously, emotional intelligence, work stress, and job satisfaction significantly influence employee performance. These findings affirm the importance of managing emotional aspects, work stress, and job satisfaction in efforts to enhance employee performance within government institutions.